Effect of Salinity on Embryo and Larval Development of Oyster Crassostrea iredalei - Amelia Ng Phei Fang; Teh Chiew Peng; Poi Khoy Yen; Zulfigar Yasin; Aileen Tan Shau Hwai (Tropical Life Sciences Research, 2016)
The effects of salinity on the embryonic and larvae stage of Crassostrea iredalei were investigated. Fertilised eggs and one day old D-larvae were subjected to salinities ranging from 0 to 30 ppt at temperature of 30±2°C. At salinity lower than 10 ppt, 100% mortality was observed. For embryo development, the highest survival was observed at salinity 25 ppt with 80.9±2.2% survival with no significant difference compared to 15 and 30 ppt. Shell height and length were both greatest at salinity 30 ppt. Throughout the 11 days culture, the highest larval survival occurred at salinity 15 ppt with no significant difference compared to all other salinities except 10 ppt. Larval shell sizes showed no significant differences between salinities, except for 10 ppt. Optimum culture condition for larvae growth are salinities ranging from 15 to 30 ppt whereby the larval of this species can tolerate wider range of salinity compared to other oyster species and thus, making it a competitive species to be cultured.